Maqasid al-Shariah in the Hajj Tanazul Policy: Public Maslahah for Elderly Indonesian Hajj Pilgrims - Wilnan Fatahillah; Hari Winarsa; Dedi Uska; Ricke Riyadi Sadikin; Islahuddin Islahuddin (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2026)
The rising share of elderly and high-risk pilgrims has made mobility management at Mina a central problem of Indonesian Hajj governance. This study aims to analyze the implementation of the Tanazul policy, the scheme that permits pilgrims to return to their transit hotels in Makkah rather than stay overnight in the Mina tents, and to assess the extent to which the policy aligns with maqasid al-shariah. The study used qualitative document-based library research combined with a juridical-normative reading of policy documents, and traced the scheme from its codification in Director General Decree Number 137 of 2025, through its postponement during the 1446/2025 season, to its full implementation for 76,412 pilgrims in 1447/2026. The findings showed that Tanazul served as a valid instrument of priority jurisprudence, in which the preservation of life was advanced to secure the preservation of religion, and that participation left the pilgrimage's validity intact. The 2025 postponement was itself consistent with maqasid reasoning because individual benefit was subordinated to preventing wider public harm. The study contributes to maqasid scholarship by showing that the framework legitimizes not only the granting of a concession but also its justified deferral, and it offers Hajj administrators a criterion for judging when a concession is safe to exercise at scale.